Microscopic image analysis techniques for the morphological characterization of pharmaceutical particles: Influence of the software, and the factor algorithms used in the shape factor estimation - Almeida-Prieto, Sergio; Blanco-Méndez, José; Otero-Espinar, Francisco J. (European journal of pharmaceutics and biopharmaceutics, 2007)
The present report highlights the difficulties of particle shape characterizations of multiparticulate systems obtained using different image analysis techniques. The report describes and discusses a number of shape factors that are widely used in pharmaceutical research. Using photographs of 16 pellets of different shapes, obtained by extrusion–spheronization, we investigated how shape factor estimates vary depending on method of calculation, and among different software packages. The results obtained indicate that the algorithms used (both for estimation of basic dimensions such as perimeter and maximum diameter, and for estimation of shape factors on the basis of these basic dimensions) have marked influences on the shape factor values obtained. These findings suggest that care is required when comparing results obtained using different image analysis programs.